Jerzego Ziomka teoria aktora i aktorstwa - HENDRYKOWSKI, MAREK (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Jerzy Ziomek’s theory of the actor and acting Marek Hendrykowskis article presents Jerzy Ziomeks pioneering theory of the way that the actor functions in the system of signs, which was published nearly half a century ago in the “Dialog” [Dia- logue] monthly. It refers both to the history and the contemporary development of the performing arts.